Locus of Control and Time and Study Management as Predictors of Academic Achievement - O. Ahmed (University of Sofia, 2018)
As contradictions among past studies on the effect of locus of control on academic achievement and dearth of researches on the effect of time and study management on academic achievement in Bangladeshi context, the present study was aimed to investigate the effect of locus of control, and time and study management in predicting academic achievement in Bangladeshi context. Study population was secondary school students, of whom a sample of 113 respondents was selected through multi-stages sampling techniques. Findings revealed significant positive correlation among locus of control, time and study management, and academic achievement. Locus of control, and time and study management environment explained 42.5% of variance of academic achievement. Findings also suggested that locus of control, and time and study management were significant predictors of academic achievement and both variables had positive effect on academic achievement.